2022
DOI: 10.1101/2022.12.07.519456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhythmic Entrainment Echoes in Auditory Perception

Abstract: Rhythmic entrainment echoes, rhythmic brain responses that outlast rhythmic stimulation, can evidence endogenous neural oscillations entrained by the stimulus rhythm. We here tested for such echoes in auditory perception. Participants detected a pure tone target, presented at a variable delay after another pure tone that was rhythmically modulated in amplitude. In four experiments involving 154 participants, we tested (1) which stimulus rate produces the strongest entrainment echo and (2), inspired by audition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…These neural ‘echoes’ are also seen in corresponding perceptual data, changing rhythmically after a rhythmic acoustic stimulus (Saberi & Hickok, 2023). This effect is observed for acoustic rhythms between 2 and 8 Hz (Farahbod et al, 2020; L'Hermite & Zoefel, 2023), suggesting an involvement of neural dynamics with similar constrained temporal flexibility as described above. A recent study suggested similar echoes produced by speech prosody at lower frequencies, confirming their relevance for speech processing (Lamekina & Meyer, 2023).…”
Section: Properties Of Neural Dynamics In the Auditory System (And Be...mentioning
confidence: 55%
See 2 more Smart Citations
“…These neural ‘echoes’ are also seen in corresponding perceptual data, changing rhythmically after a rhythmic acoustic stimulus (Saberi & Hickok, 2023). This effect is observed for acoustic rhythms between 2 and 8 Hz (Farahbod et al, 2020; L'Hermite & Zoefel, 2023), suggesting an involvement of neural dynamics with similar constrained temporal flexibility as described above. A recent study suggested similar echoes produced by speech prosody at lower frequencies, confirming their relevance for speech processing (Lamekina & Meyer, 2023).…”
Section: Properties Of Neural Dynamics In the Auditory System (And Be...mentioning
confidence: 55%
“…Brain imaging revealed that blood‐oxygen level dependent (BOLD) responses to amplitude modulated (AM) sounds are strongest if these are presented at 4–5 Hz (Giraud et al, 2000; Tanaka et al, 2000). Rhythmic AM sounds also give rise to rhythmic fluctuations in auditory sensitivity that outlast the stimulus, but only at rates between ~2 and 8 Hz (Farahbod et al, 2020; Hickok et al, 2015; L'Hermite & Zoefel, 2023). Non‐rhythmic acoustic stimuli, such as the onset of broadband noise, produce similar fluctuations in neural dynamics and auditory sensitivity in the delta–theta range, although the exact frequency remains unclear (~1–2 Hz in Kayser, 2019; ~5 Hz in Teng et al, 2018; ~6–8 Hz in Ho et al, 2017).…”
Section: Properties Of Neural Dynamics In the Auditory System (And Be...mentioning
confidence: 99%
See 1 more Smart Citation